2019
DOI: 10.31234/osf.io/hj7f9
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reaching for an object or that object: Context and limitations in encoding object features may constrain infant goal attribution

Abstract: That very young infants attribute goals to the object-directed reaches of others is well characterized, but we understand little of what infants encode about the objects being acted on. The present study examined whether the context surrounding the reach, specifically the presence of another object, prompts infants to encode feature information of the target object. To test this, 9-month-old infants in Experiment 1 observed an actor repeatedly reach for one of two objects, while in Experiment 2, infants obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
3
1
Order By: Relevance
“…It is noteworthy that, in Experiment 2, after familiarization with a reaching event involving a single object, infants looked longer in test at actions directed toward this object compared to a new object. Such a pattern, however, was not reported in other studies using similar familiarization, where children were found to look equally at the two events 26,33,37,39 . Thus, this pattern is likely to reflect specific features of our procedure.…”
Section: Methodscontrasting
confidence: 67%
See 3 more Smart Citations
“…It is noteworthy that, in Experiment 2, after familiarization with a reaching event involving a single object, infants looked longer in test at actions directed toward this object compared to a new object. Such a pattern, however, was not reported in other studies using similar familiarization, where children were found to look equally at the two events 26,33,37,39 . Thus, this pattern is likely to reflect specific features of our procedure.…”
Section: Methodscontrasting
confidence: 67%
“…For example, when infants are presented with multiple repetitions of a scene where a hand grasped one of two potential goal-objects, they expect that the agent will choose the same object again in new situations 35 . These results suggest that observing choices can serve as the basis for the attribution of a positive disposition toward the chosen object in early infancy 36,37 .…”
mentioning
confidence: 79%
See 2 more Smart Citations